2018
DOI: 10.4293/jsls.2018.00026
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Endoscopic Thyroidectomy: A Systematic Review of the Practice So Far

Abstract: Background and Objectives:Thyroid disease largely affects young females, but the incidence is also increasing among males. In an effort to avoid the scarring of the neck that is synonymous with conventional thyroidectomy, endoscopic techniques have been developed over the years. The transoral endoscopic approach is the latest of these innovations that promises a scarless surgical outcome. This review evaluates whether this technique is safe and feasible in live patients and outlines the outcomes in published l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 46 publications
2
40
2
3
Order By: Relevance
“…However, numerous publications from Thailand, Korea, China, and the United States have reported only few wound infections after transoral vestibular endoscopic and robotic thyroidectomy . Rates of surgical site infection in the meta‐analyses were also very low (0.1%‐1%) . There is no standard definition of surgical site infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, numerous publications from Thailand, Korea, China, and the United States have reported only few wound infections after transoral vestibular endoscopic and robotic thyroidectomy . Rates of surgical site infection in the meta‐analyses were also very low (0.1%‐1%) . There is no standard definition of surgical site infection.…”
Section: Discussionmentioning
confidence: 94%
“…The most important priority in evaluating and adopting a new surgical procedure is its safety. In recent studies, including four meta‐analyses, transoral endoscopic and robotic thyroidectomy has been reported to be safe and comparable to conventional transcervical thyroidectomy . However, most studies of transoral thyroidectomy are case series with relatively small sample sizes, and there are only a few studies involving more than 100 cases .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the safety and feasibility of this technique in both benign and malignant lesions of the thyroid. 4,5 As this procedure only requires some of the basic endoscopic instruments, TOETVA can be broadly applied to plenty of health facilities worldwide, even in places whose medical facilities have not developed yet. 6 Furthermore, the learning curve for TOETVA appears to be relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…Scarless neck surgery to remove the thyroid or parathyroid glands, through various robotic and endoscopic approaches, has garnered increasing attention over the past decade. 1 In particular, transoral endoscopic thyroidectomy via a vestibular approach (TOETVA) is lauded as the least invasive of the remote access thyroidectomy approaches because it makes use of a natural orifice and avoids skin incisions entirely. 2,3 Numerous studies have demonstrated the safety and efficacy of TOETVA compared to alternate scarless approaches as well as to traditional open neck surgery in the appropriate patient population.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Numerous studies have demonstrated the safety and efficacy of TOETVA compared to alternate scarless approaches as well as to traditional open neck surgery in the appropriate patient population. 1,4,5 As indications for the transoral approaches expand, 6,7 studies to further understand its impact on patient outcomes is warranted.…”
Section: Introductionmentioning
confidence: 99%